Porous film

By adjusting the combination and film-making conditions of polyolefin-based resin and styrene-based thermoplastic elastomer, combining styrene-olefin-styrene block copolymer, a porous film with excellent breathability and mechanical properties is formed, and the prior art is solved The problem of difficulty in taking into account both breathable and mechanical characteristics.

CN119256044APending Publication Date: 2025-01-03MITSUBISHI CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041331.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When the existing porous films improve breathable characteristics, it is easy to cause mechanical strength to decrease, uneven bonding or rupture of the film during film formation, making it difficult to take into account both breathable and mechanical characteristics.

Method used

By adjusting the combination of polyolefin-based resin and styrene-based thermoplastic elastomer and film-making conditions, the tensile strength and elongation of the porous film reach a specific value and combine with styrene-olefin-styrene block copolymer Use to form a uniform and efficient porous structure.

Benefits of technology

A porous film that takes into account both breathable and mechanical characteristics when it is not easy to cause uneven adhesion or rupture of the film is achieved, ensuring that the thickness and strength of the film meet the requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140828900000211
    Figure BDA0005140828900000211
  • Figure BDA0005140828900000221
    Figure BDA0005140828900000221
Patent Text Reader

Abstract

A porous film according to one embodiment of the present invention contains a polyolefin resin (A) and a styrene thermoplastic elastomer (B), and has a thickness (T) of 50 [mu] m or less, an average tensile strength of 15 MPa or more, an average tensile elongation at break of 35% or more, and a ratio (S / T) of air permeability S (sec / 100 cc) to thickness T ([mu] m) of 0.15-1.45.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to porous films. Background Art

[0002] Polymer porous films having a large number of fine interconnected pores are used in various fields, such as separation membranes used in the production of ultrapure water, purification of chemical solutions, water treatment, etc., waterproof and breathable films used in clothing and sanitary materials, or separators used in electronic components such as capacitors, batteries, and electrolytic capacitors.

[0003] Among them, the porous film formed by the polyolefin resin is manufactured by the following methods: a method in which the crystallization of the polyolefin resin is controlled during the cooling and solidification process of the melt extrusion, and the film of the crystallized polyolefin resin is stretched to make it porous; a method in which a polyolefin molded body in which heterogeneous solids are finely dispersed is subjected to strain such as stretching to create pores between the heterogeneous solids to make it porous; or a method in which micropowders of heterogeneous polymers, alkanes, waxes, etc. are finely dispersed in the polyolefin resin and then they are subjected to solvent extraction.

[0004] Patent Documents 1 and 2 propose the following technology: a polypropylene resin is used as a matrix, a styrene-based thermoplastic elastomer that shows partial compatibility with the matrix is ​​used as a domain for compounding, melt extrusion is performed from a T-die, melt solidification is performed with a casting roll, thereby obtaining a sheet-like object, and the obtained sheet-like object is subjected to biaxial stretching to thereby obtain a stretched porous film. In these technologies, the porous structure can be adjusted according to the type of the styrene-based thermoplastic elastomer.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-141786

[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-222823 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] Examples of methods for improving the air permeability of a porous film include increasing the porosity of the film (increasing the number of interconnected pores) and reducing the thickness of the film.

[0011] Moreover, as methods for increasing the porosity, there can be cited: a method of increasing the crystallinity of the matrix resin by increasing the casting temperature, etc.; a method of increasing the longitudinal and transverse stretching ratios and adjusting the longitudinal: transverse stretching ratio; a method of using an elastomer with high viscosity; a method of using an elastomer with low compatibility with the matrix resin, etc.

[0012] However, if the porosity is increased excessively, the mechanical strength of the film decreases, which may make the film unsuitable for practical use.

[0013] On the other hand, it is known that when an attempt is made to improve the air permeability by thinning the film and increasing the porosity by the above method, uneven adhesion with the casting roll and film breakage may occur during film formation.

[0014] Therefore, an object of the present invention is to provide a film which is less likely to cause uneven adhesion or film breakage during film formation and which has both air permeability and mechanical properties.

[0015] Solutions for solving problems

[0016] The present inventors have conducted in-depth studies in view of the above-mentioned problems, and as a result, by adjusting the combination of polyolefin resin and styrene thermoplastic elastomer, film-making conditions, etc. in a manner so that the tensile strength of the film after pores are formed becomes above a specific value, they have successfully obtained a film that is not prone to uneven adhesion or film breakage even when the film thickness is thin, and that takes into account both air permeability and mechanical properties, thereby completing the present invention.

[0017] The present invention relates to the following.

[0018] [1] A porous film comprising a polyolefin resin (A) and a styrene-based thermoplastic elastomer (B),

[0019] The porous film has a thickness (T) of less than 50 μm, an average tensile strength of more than 15 MPa, an average tensile elongation at break of more than 35%, and a ratio (S / T) of air permeability (S) (seconds / 100 cc) to thickness (T) (μm) of more than 0.15 and less than 1.45.

[0020] [2] The porous film according to [1] above, which has an average tensile strength of 25 MPa or more.

[0021] [3] The porous film according to [1] or [2] above, wherein the polyolefin-based resin (A) is homopolypropylene.

[0022] [4] A porous film according to any one of [1] to [3] above, wherein the aforementioned styrene-based thermoplastic elastomer (B) contains a styrene-olefin-styrene block copolymer (B2) in a proportion of 50% by mass or more when the total amount of the styrene-based thermoplastic elastomer (B) is set to 100% by mass.

[0023] [5] The porous film according to any one of [1] to [4] above, wherein the styrene content of the styrene-based thermoplastic elastomer (B) is 10% by mass or more and 40% by mass or less.

[0024] [6] A porous film according to any one of [1] to [5] above, wherein the aforementioned styrene-based thermoplastic elastomer (B) contains a resin having a weight average molecular weight (Mw) of 200,000 or more in a proportion of 50% by mass or more when the total amount of the styrene-based thermoplastic elastomer (B) is set to 100% by mass.

[0025] [7] A porous film according to any one of [1] to [6] above, wherein the aforementioned styrene-based thermoplastic elastomer (B) contains a resin having a melt flow rate (MFR) of less than 0.1 g / 10 min or a non-flowing resin measured at a temperature of 200°C and a load of 10 kg, in a proportion of 50% by mass or more when the total amount of the styrene-based thermoplastic elastomer (B) is set to 100% by mass.

[0026] [8] A porous film according to any one of [1] to [7] above, wherein the styrene-based thermoplastic elastomer (B) comprises a styrene-olefin copolymer (B1) and a styrene-olefin-styrene block copolymer (B2), and the melt flow rate (MFR) of the styrene-olefin copolymer (B1) measured at a temperature of 200°C and a load of 10 kg is greater than 1.0 g / 10 min.

[0027] [9] The porous film according to any one of [1] to [8] above, wherein the content of the polyolefin-based resin (A) is 60% by mass or more and 95% by mass or less.

[0028]

[10] The porous film according to any one of [1] to [9] above, wherein the content of the styrene-based thermoplastic elastomer (B) is 5% by mass or more and 40% by mass or less.

[0029]

[11] The porous film according to any one of [1] to

[10] above, further comprising a crystal nucleating agent (C).

[0030]

[12] The porous film according to any one of [1] to

[11] above, wherein the air permeability (S) is 50 sec / 100 cc or less.

[0031]

[13] A separator for an electricity storage device, comprising the porous film according to any one of [1] to

[12] above.

[0032]

[14] An electricity storage device comprising the separator for an electricity storage device according to

[13] above.

[0033] Effects of the Invention

[0034] The porous film of the present invention is unlikely to cause uneven adhesion, film breakage, etc. during film production, and can achieve both air permeability and mechanical properties. DETAILED DESCRIPTION

[0035] Hereinafter, a porous film and a method for producing the same will be described in detail as an example of an embodiment of the present invention, but the scope of the present invention is not limited to the embodiment described below.

[0036] It should be noted that the "film" in the present invention conceptually includes sheets and films.

[0037] In the present invention, when "x to y" is expressed (x and y are arbitrary numbers), unless otherwise specified, it includes the meaning of "x or more and y or less", as well as the meaning of "preferably greater than x" or "preferably less than y".

[0038] In addition, when expressed as "x or more" (x is an arbitrary number), unless otherwise specified, it also includes the meaning of "preferably greater than x", and when expressed as "y or less" (y is an arbitrary number), unless otherwise specified, it also includes the meaning of "preferably less than y".

[0039] Furthermore, "x and / or y (x and y are arbitrary structures)" means at least one of x and y, and means three types: only x, only y, and x and y.

[0040] <Resin composition>

[0041] The porous film of the present invention (hereinafter also referred to as "the present film") is preferably formed from a resin composition (hereinafter also referred to as "the present composition") containing at least a polyolefin-based resin and a styrene-based thermoplastic elastomer.

[0042] Hereinafter, the components constituting the present composition will be described in detail.

[0043] 1. Polyolefin resin (A)

[0044] Examples of the polyolefin resin (A) include: homopolypropylene (propylene homopolymer), or a polypropylene resin such as a random copolymer or block copolymer of propylene and an α-olefin such as ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene or 1-decene; a polyethylene resin such as a high-density polyethylene (HDPE), a linear low-density polyethylene (LLDPE), a low-density polyethylene (LDPE), a random copolymer or block copolymer of ethylene and an α-olefin such as 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene or 1-decene; and modified products of the above-mentioned polypropylene resins or polyethylene resins modified with functional groups such as acid anhydrides.

[0045] The polyolefin-based resins (A) exemplified above may be used alone or in combination of two or more.

[0046] Among them, polypropylene-based resins are preferred, and homopolypropylene is more preferred from the viewpoint of mechanical strength.

[0047] When a polypropylene resin is used as the polyolefin resin (A), the isotactic pentad fraction is not particularly limited, preferably 80 mol% or more and 99 mol% or less, more preferably 83 mol% or more and 98 mol% or less, and further preferably 85 mol% or more and 97 mol% or less. The isotactic pentad fraction reflects stereoregularity. If the isotactic pentad fraction is too low, there is a concern that sufficient porosity cannot be achieved by stretching. On the other hand, the upper limit of the isotactic pentad fraction is limited by the upper limit value currently obtained in industry, but it is not limited thereto when a resin with further high regularity is developed at an industrial level in the future.

[0048] The isotactic pentad fraction refers to the stereostructure or ratio in which the five methyl groups as side chains are all located in the same direction for a main chain based on carbon-carbon bonds composed of any five consecutive propylene units. The attribution of the signal in the methyl region is based on A. Zambelli et al., Macromol., 8, 687 (1975).

[0049] The Mw / Mn of the polyolefin resin (A) is not particularly limited, preferably 1.5 or more and 10.0 or less, more preferably 2.0 or more and 8.0 or less, and further preferably 2.0 or more and 6.0 or less. Mw / Mn is a parameter representing molecular weight distribution, and the smaller the Mw / Mn, the narrower the molecular weight distribution. By making Mw / Mn above the above lower limit, sufficient extrusion moldability can be obtained, and industrial mass production can be achieved. On the other hand, by making Mw / Mn below the above upper limit, sufficient mechanical strength can be ensured.

[0050] In addition, Mw / Mn in the present invention is a value measured by GPC (gel permeation chromatography) method.

[0051] The melt flow rate (MFR) of the polyolefin resin (A) is not particularly limited, but is preferably 0.5 g / 10 min or more and 15 g / 10 min or less, more preferably 1.0 g / 10 min or more and 10 g / 10 min or less, and further preferably 1.5 g / 10 min or more and 8 g / 10 min or less. By setting the MFR to be above the lower limit, sufficient melt viscosity can be obtained during molding, thereby ensuring high productivity. On the other hand, by setting the MFR to be below the upper limit, sufficient strength can be obtained.

[0052] In addition, the MFR of the polyolefin-based resin (A) in the present invention is a value measured under the conditions of a temperature of 230° C. and a load of 2.16 kg in accordance with JIS K7210-1 (2014).

[0053] As the polyolefin-based resin (A), for example, commercially available products such as "NOVATEC PP" and "WINTEC" (manufactured by Japan Polypropylene Co., Ltd.); "Notio" and "Tafmer XR" (manufactured by Mitsui Chemicals, Inc.); "Zelas" and "Thermorun" (manufactured by Mitsubishi Chemical Corporation); "Sumitomo Noblen" and "Tafthren" (manufactured by Sumitomo Chemical Co., Ltd.); "Prime PP" and "Prime TPO" (manufactured by Prime Polymer Co., Ltd.); "Adflex", "Adsyl" and "HMS-PP (PF814)" (manufactured by SunAllomer Ltd.); "Versify" and "Inspire" (manufactured by Dow Chemical Co., Ltd.) can be used.

[0054] The content of the polyolefin resin (A) in the present composition is preferably 60% by mass or more and 95% by mass or less, more preferably 65% ​​by mass or more and 90% by mass or less, and further preferably 65% ​​by mass or more and 85% by mass or less. If the content of the polyolefin resin (A) is within the above range, a sea-island structure having the polyolefin resin (A) as a matrix and the styrene-based thermoplastic elastomer (B) as a domain can be formed, and a porous structure can be easily formed when stretched.

[0055] 2. Styrene-based thermoplastic elastomer (B)

[0056] The film is as follows: a styrene-based thermoplastic elastomer (B) is added to a polyolefin-based resin (A) to form an island structure in which the styrene-based thermoplastic elastomer (B) forms domains in the matrix of the polyolefin-based resin (A), thereby efficiently obtaining a porous film having a fine and highly uniform porous structure, making it easy to control the shape and pore size of the pores.

[0057] The styrene-based thermoplastic elastomer (B) is a type of thermoplastic elastomer based on a styrene component, and is a copolymer formed by a continuum of a soft component (e.g., a butadiene component) and a hard component (e.g., a styrene component). Specifically, the copolymer is hydrogenated so that the carbon double bonds are converted into single bonds.

[0058] In addition, examples of the types of the copolymer include random copolymers, block copolymers, and graft copolymers.

[0059] In addition, examples of the block copolymer include a linear block structure and a radially branched block structure, and any structure may be adopted in the present invention.

[0060] As styrene-based thermoplastic elastomers (B), for example, styrene-olefin copolymers (B1) and styrene-olefin-styrene copolymers (B2) can be cited. As styrene-olefin copolymers (B1), for example, styrene-butadiene copolymers (SBR), hydrogenated styrene-butadiene copolymers (SEB), styrene-isoprene copolymers (SIR), styrene-ethylene-propylene copolymers (SEP), etc. can be cited. As styrene-olefin-styrene copolymers (B2), for example, styrene-butadiene-styrene copolymers (SBS), styrene-butadiene-butylene-styrene copolymers (SBBS), styrene-ethylene-butadiene-styrene copolymers (SEBS), styrene-isoprene-styrene copolymers (SIS), styrene-ethylene-propylene-styrene copolymers (SEPS), styrene-ethylene-ethylene-propylene-styrene copolymers (SEEPS), etc. can be cited.

[0061] The styrene-based thermoplastic elastomer (B) exemplified above may be used alone or in combination of two or more.

[0062] Among the above, if the compatibility with the polyolefin resin (A) is low, there is a tendency to easily form a porous structure. Therefore, from the viewpoint of the formation of the porous structure, it is preferred to use a resin having a structure in which both ends are styrene polymers as the main component. On the other hand, in order to efficiently disperse the styrene-based thermoplastic elastomer (B) in the present composition, it is preferred to use an ethylene component (hydrogenated butadiene component), an ethylene·propylene component (hydrogenated isoprene component), or a resin containing a butene component that has high compatibility with the polyolefin resin (A) as the main component.

[0063] That is, from the perspective of the formation of a porous structure, it is preferred to use styrene-olefin-styrene copolymer (B2) as the main component, and from the perspective of the dispersibility of the styrene-based thermoplastic elastomer (B), it is preferred to use SEP, SEPS or SEBS as the main component. From the above two perspectives, it is more preferred to use SEPS or SEBS as the main component, among which SEPS is particularly preferred as the main component.

[0064] It should be noted that the "main component" in the styrene-based thermoplastic elastomer (B) refers to the resin with the largest content of the styrene-based thermoplastic elastomer (B) contained in the present composition. More specifically, when the total amount of the styrene-based thermoplastic elastomer (B) is set to 100% by mass, 100% by mass is taken as the upper limit, and the resin preferably accounts for 50% by mass or more, more preferably 60% by mass or more, and further preferably 65% ​​by mass or more.

[0065] Among the above, the styrene-based thermoplastic elastomer (B) contained in the present composition preferably includes a styrene-olefin copolymer (B1) and a styrene-olefin-styrene block copolymer (B2) from the viewpoint of achieving a higher level of both air permeability and mechanical properties.

[0066] Furthermore, the styrene-olefin copolymer (B1) preferably has a melt flow rate (MFR) of 1.0 g / 10 min or more as measured at a temperature of 200° C. and a load of 10 kg.

[0067] Generally, when a porous film is made thinner or its porosity is increased in order to improve its air permeability, there are problems such as deterioration of film forming properties and reduction of mechanical strength.

[0068] The present inventors have repeatedly studied based on the above situation. As a result, it is found that by combining two specific styrene-based thermoplastic elastomers (B), the uniformity of the porous structure obtained by the stretching process is improved, and as a result, a porous film having excellent film-forming properties, mechanical strength and air permeability can be provided even if the film thickness is thin.

[0069] The above-mentioned effects are considered to be exhibited by the following mechanism.

[0070] The pores in the porous film of the present invention are mainly formed in the domain of the styrene-based thermoplastic elastomer (B) and are formed starting from the cracks generated during stretching. The structure of the domain is closely related to the porous structure. The larger the domain, the larger the pores and the better the air permeability.

[0071] Among the styrene-based thermoplastic elastomers (B), styrene-olefin-styrene copolymers (B2) are preferred because a large domain can be easily obtained.

[0072] On the other hand, the styrene-olefin-styrene copolymer (B2) has low compatibility with the polyolefin-based resin (A) forming the matrix, and the efficiency of cracking inside the domain, which serves as the starting point of opening the pores during pore formation, is insufficient.

[0073] Therefore, it is considered that by using a styrene-olefin copolymer (B1) having high compatibility with the polyolefin-based resin (A) together with the aforementioned styrene-olefin-styrene copolymer (B2), the aforementioned styrene-olefin copolymer (B1) also acts as a compatibilizer, improves the adhesion between the matrix and the domain interface, and promotes the formation of pores inside the domain.

[0074] Furthermore, the styrene-olefin copolymer (B1) is localized on the surface of the domain, so that the dispersibility of the domain is improved and the uniformity of the porous structure is increased, thereby improving the mechanical properties.

[0075] Furthermore, inside the domains, pores based on the styrene-olefin copolymer (B1) are formed between large pores formed by the styrene-olefin-styrene copolymer (B2), thereby improving the connectivity of the pores and further improving the air permeability characteristics.

[0076] From the above viewpoints, the melt flow rate (MFR) of the styrene-olefin copolymer (B1) measured at a temperature of 200°C and a load of 10 kg is more preferably 1.2 g / 10 min or more, further preferably 1.4 g / 10 min or more, and further preferably 1.6 g / 10 min or more.

[0077] The styrene content of the styrene-based thermoplastic elastomer (B) is preferably 10% by mass or more and 40% by mass or less, more preferably 10% by mass or more and 35% by mass or less. If the styrene content is above the lower limit, domains can be effectively formed in the polyolefin-based resin (A), and if the styrene content is below the upper limit, excessively large domain formation can be suppressed.

[0078] In addition, when there are two or more types of styrene-based thermoplastic elastomers (B) contained in the present composition, the above-mentioned styrene content refers to the total amount of the entire styrene-based thermoplastic elastomer (B).

[0079] The weight average molecular weight (Mw) of the resin serving as the main component of the styrene-based thermoplastic elastomer (B) contained in the present composition is not particularly limited, but is preferably 200,000 or more, more preferably 250,000 or more and 1,000,000 or less, more preferably 250,000 or more and 800,000 or less, and further preferably 250,000 or more and 600,000 or less.

[0080] The Mw / Mn of the resin serving as the main component in the styrene-based thermoplastic elastomer (B) contained in the present composition is not particularly limited, but is preferably 1.00 to 1.50, more preferably 1.00 to 1.40, and further preferably 1.05 to 1.20.

[0081] When a film formed from the present composition is stretched in at least one uniaxial direction to be porous, the morphology of the polypropylene resin (A) and the styrene thermoplastic elastomer (B) in the resin composition before stretching becomes an important factor in forming the porous structure.

[0082] Specifically, it is important that the styrene-based thermoplastic elastomer (B) present as domains in the matrix containing the polypropylene-based resin (A) as a main component exists in a spherical shape.

[0083] Generally, when the resin composition having the sea-island structure of the matrix / domain is melt-extruded and cooled and solidified, the resin composition flowing by extrusion from a shaping device such as a spinneret or a nozzle is cooled and solidified by a cooling and solidifying device such as a casting roll (cooling roll), air cooling, or water cooling. At this time, the resin composition melts and elongates in the gap (gap) between the shaping device and the cooling and solidifying device, so when the weight average molecular weight of the styrene-based thermoplastic elastomer (B) as the domain is small, a resin composition in which the domain is elongated in the flow direction (extrusion direction) is obtained.

[0084] Then, if the domain is extended in the flow direction (extrusion direction), the area of ​​the domain particles in the flow direction becomes larger. Therefore, it becomes difficult to cause cracking inside the domain for the stress in the flow direction (extrusion direction), and sometimes a porous structure cannot be fully formed.

[0085] On the other hand, when the weight average molecular weight of the styrene-based thermoplastic elastomer (B) as the domain is large, the domain is not easily affected by melt elongation, and the domain in the obtained resin composition before stretching tends to remain spherical. If the domain is spherical, it becomes easy to cause cracking inside the domain for the stress in the flow direction (extrusion direction), so it is believed that a porous structure is fully formed.

[0086] Furthermore, generally, the higher the molecular weight, the higher the tensile strength tends to be. Therefore, further improvement in tensile strength is expected by selecting a resin having a high weight average molecular weight (Mw) as the main component of the styrene-based thermoplastic elastomer (B).

[0087] Therefore, it is preferred that the weight average molecular weight (Mw) of the resin serving as the main component of the styrene-based thermoplastic elastomer (B) be within the above range.

[0088] When the ratio (molecular weight distribution) Mw / Mn of the number average molecular weight Mn to the weight average molecular weight (Mw) of the resin serving as the main component in the styrene-based thermoplastic elastomer (B) is within the above range, the dispersion diameter of the formed domains tends to become uniform, which is more preferred.

[0089] The melt flow rate (MFR) of the resin serving as the main component of the styrene-based thermoplastic elastomer (B) contained in the present composition is not particularly limited, but is preferably lower than 0.1 g / 10 min or does not flow.

[0090] In addition, the MFR of the styrene-based thermoplastic elastomer (B) in the present invention is a value measured under the conditions of a temperature of 200° C. and a load of 10 kg in accordance with JIS K7210-1 (2014).

[0091] The shape of the styrene thermoplastic elastomer (B) dispersed in the resin composition changes depending on the viscosity difference with the polyolefin resin (A), but when a styrene thermoplastic elastomer having an MFR within the above range is used as the main component, the shape tends to be spherical.

[0092] Unlike domains with a large aspect ratio, spherically dispersed domains are preferred because the uniformity of the porous structure obtained in the subsequent stretching step is likely to be high and the physical property stability is excellent.

[0093] Furthermore, when a styrene-based thermoplastic elastomer having an MFR within the above range is used as a main component, stress is easily concentrated inside the domain during the stretching step, so that a cell opening starting point is easily generated and porosification is easily achieved.

[0094] The content of the styrene-based thermoplastic elastomer (B) in the present composition is preferably 5% by mass or more and 40% by mass or less, more preferably 10% by mass or more and 37% by mass or less, and further preferably 15% by mass or more and 35% by mass or less. When the content of the styrene-based thermoplastic elastomer (B) is within the above range, a sea-island structure having the polyolefin-based resin (A) as a matrix and the styrene-based thermoplastic elastomer (B) as a domain can be formed, and a porous structure can be easily formed when stretched.

[0095] 3. Crystallization nucleating agent (C)

[0096] When the present composition is made porous by stretching between the polyolefin resin (A) and the styrene-based thermoplastic elastomer (B), increasing the rigidity of the polyolefin resin (A) is considered effective for pore formation, and therefore, the crystal nucleating agent (C) may be contained.

[0097] As the crystal nucleating agent (C), an α-crystal nucleating agent is preferred, and examples thereof include dibenzylidene sorbitol (manufactured by Shin Nippon Rika Co., Ltd., trade name “GEL ALL MD”), “ADK STAB NA-11”, “ADK STAB NA-27”, “ADK STAB NA-902”, “ADK STAB NA-21”, and “ADK STAB NA-71” (the five on the left are all manufactured by ADEKA Co., Ltd.), a masterbatch containing a mixture of magnesium stearate and silicon dioxide (manufactured by Dainichi Seika Industries, Ltd., trade name “HI-CYCLEMASTER”), and a masterbatch containing the sodium salt of 2-hydroxy-2-oxo-4,6,10,12-tetra-tert-butyl-1,3,2-dibenzo[d,g]perhydrodioxaphosphocene (manufactured by ADEKA Co., Ltd., trade name “ADK STAB M-701”).

[0098] In addition, for α crystal nucleating agents, as inorganic nucleating agents, silicon dioxide, talc, and calcium carbonate can be cited. As organic systems (carboxylic acid metal salt type), calcium stearate, sodium benzoate, aluminum benzoate, aluminum dibenzoate, potassium benzoate, lithium benzoate, sodium β-naphthoate, sodium cyclohexanecarboxylate, pimelic acid metal salts, rosin acid metal salts, etc. can be cited. In addition, there are also benzylidene sorbitol and its derivative type, phosphate metal salts. Furthermore, as polymer type, poly-3-methyl-1-butene, polyvinyl cycloalkane, polyvinyl trialkylsilane, EPR, Kevlar fiber, 2,2'-methylenebis (4,6-di-tert-butylphenyl) sodium phosphate, etc. can be cited.

[0099] The content of the α-crystal nucleating agent in the present composition is preferably 0.001 parts by mass or more and 10 parts by mass or less, more preferably 0.005 parts by mass or more and 5 parts by mass or less, further preferably 0.01 parts by mass or more and 2 parts by mass or less, and further preferably 0.05 parts by mass or more and 1.5 parts by mass or less, relative to 100 parts by mass of the resin component in the present composition. When the content of the α-crystal nucleating agent is less than 0.001 parts by mass, there is a possibility that the formation of α crystals becomes insufficient. On the other hand, when the content of the α-crystal nucleating agent is more than 10 parts by mass, there is a concern that the α-crystal nucleating agent may seep out or precipitate scale, powder fall, etc. in the film forming process, the secondary processing process, etc., and there is also a possibility that the cost may increase.

[0100] 4. Other ingredients

[0101] The composition may contain various additives such as heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, colorants, antistatic agents, hydrolysis inhibitors, lubricants, flame retardants, etc. as long as the properties are not impaired. Other resins may also be contained as long as the properties are not impaired.

[0102] Furthermore, in the present composition, within the scope not impairing the present invention, surface processing such as corona treatment, plasma treatment, printing, coating, and vapor deposition may be performed as needed, and perforation processing may be performed, and multiple porous films of the present invention may be overlapped and used according to the application.

[0103] <Porous film>

[0104] The present film may be formed only of the porous layer composed of the above-mentioned resin composition, or other layers may be laminated thereon within a range not hindering the characteristics of the present invention.

[0105] It should be noted that the "porous film" in the present invention means a film having a porosity of 50% or more, preferably 55% or more, more preferably 60% or more. When the film has a layer other than the porous layer, the porosity of the porous layer alone may be within the above range.

[0106] The porosity can be calculated from the density of the resin composition by the method described in Examples.

[0107] The thickness (T) of the film is 50 μm or less. When the thickness (T) is 50 μm or less, good air permeability can be obtained.

[0108] On the other hand, in order to maintain sufficient strength as a film, the lower limit of the thickness (T) of the film is preferably 1 μm or more. From the above viewpoint, the thickness (T) of the film is preferably 1 μm or more and 50 μm or less, more preferably 2 μm or more and 30 μm or less, and further preferably 5 μm or more and 25 μm or less.

[0109] The average tensile strength of the present film is 15 MPa or more. By setting the average tensile strength of the present film to 15 MPa or more, excellent mechanical properties can be obtained.

[0110] From the above viewpoint, the average tensile strength of this film is preferably 20MPa or more, wherein, preferably 25MPa or more, more preferably 27MPa or more, further preferably 30MPa or more. The upper limit is not particularly limited, for example, it can be 400MPa or less, can be 300MPa or less, can be 200MPa or less, can be 100MPa or less.

[0111] It is preferred that the average tensile strength of the present film be equal to or less than the upper limit in terms of excellent handleability.

[0112] It should be noted that the average tensile strength in the present invention is an average value of the tensile strengths in MD and TD measured by the method described in the Examples.

[0113] The average tensile elongation at break of the film is not particularly limited, but is preferably 35% or more, more preferably 40% or more, further preferably 45% or more, and further preferably 50% or more. The upper limit is not particularly limited, but may be, for example, 200% or less.

[0114] When the average tensile elongation at break of the present film is within the above range, excellent mechanical properties can be obtained.

[0115] It should be noted that the average tensile elongation at break in the present invention is an average value of the tensile elongations at break in MD and TD measured by the method described in the Examples.

[0116] The average tensile strength and average tensile elongation at break can be adjusted according to the chemical structure, molecular weight, MFR, content, casting temperature during film formation, stretch ratio, etc. of the polyolefin resin (A) and the styrene thermoplastic elastomer (B).

[0117] For example, the average tensile strength and the average tensile elongation at break can be adjusted by using a styrene-based thermoplastic elastomer (B) having low compatibility with the polyolefin-based resin (A) as the main component; using a resin having a high weight-average molecular weight (Mw) as the main component of the styrene-based thermoplastic elastomer (B); using a resin having a low MFR (i.e., low viscosity) as the main component of the styrene-based thermoplastic elastomer (B); adjusting the content ratio of the polyolefin-based resin (A) and the styrene-based thermoplastic elastomer (B) to the above-mentioned suitable range; in the manufacturing method described later, adjusting the temperature of the casting roll during film formation to a suitable range; and in the case of biaxial stretching, adjusting the longitudinal and transverse stretch ratios and stretch ratios to a suitable range, etc.

[0118] When the scheme exemplified above is applied, not only can the morphology of the polyolefin resin (A) and the styrene thermoplastic elastomer (B) be controlled, but also the pore structure formation and film thickness can be controlled. Therefore, it is believed that the moderate formation of a porous structure will improve the air permeability properties.

[0119] The air permeability (S) of the present film is not particularly limited, but is preferably 50 sec / 100 cc or less, more preferably 40 sec / 100 cc or less, further preferably 30 sec / 100 cc or less, and further preferably 25 sec / 100 cc or less, with 0 sec / 100 cc being the lower limit.

[0120] In addition, the air permeability (S) in the present invention is measured at 25°C in accordance with JIS P8117:2009.

[0121] The ratio (S / T) of the air permeability (S) (seconds / 100cc) of the film to the thickness (T) (μm) is 0.15 or more and 1.45 or less. By making the ratio (S / T) of the air permeability (S) to the thickness (T) within the above range, a porous film with excellent air permeability characteristics can be formed. From the above viewpoint, the value of the aforementioned (S / T) is preferably 0.20 or more and 1.40 or less, more preferably 0.30 or more and 1.30 or less, further preferably 0.40 or more and 1.20 or less, and particularly preferably 0.50 or more and 1.10 or less.

[0122] The value of (S / T) can be adjusted according to the chemical structure, molecular weight, MFR, content, casting temperature and stretch ratio during film formation of the polyolefin resin (A) and the styrene thermoplastic elastomer (B).

[0123] The film preferably has a heat shrinkage of 3% or less when heated at 60°C for 1 hour. A porous film having excellent dimensional stability can be formed by having a heat shrinkage of 3% or less. From the above viewpoints, the film preferably has a heat shrinkage of 2% or less, more preferably 1% or less, further preferably 0.6% or less, and particularly preferably 0.4% or less.

[0124] In addition, the heat shrinkage rate in the present invention can be measured by the following method.

[0125] Cut out a sample with a length of 150 mm and a width of 10 mm, with the longitudinal direction (MD) and transverse direction (TD) of the film as the length direction, and mark lines at intervals of 100 mm in a manner such that the center of the length direction is centered relative to the length direction. Then, heat in an oven at 60°C for 1 hour, and measure the interval between the marked lines after shrinkage. Substitute the measured interval between the marked lines into the following formula to calculate the shrinkage rate (%). The average value of the shrinkage rates obtained for the longitudinal direction (MD) and the transverse direction (TD) is used as the heat shrinkage rate in the present invention.

[0126] Shrinkage rate (%) = ((marking line interval before shrinkage - marking line interval after shrinkage) / marking line interval before shrinkage) × 100

[0127] <Method for producing porous film>

[0128] The method for manufacturing a porous film of the present invention (hereinafter also referred to as "this method") comprises the following steps: step (I), melt-extruding a resin composition containing a polyolefin resin (A) and a styrene-based thermoplastic elastomer (B) to obtain a pre-stretched sheet; and step (II), stretching the pre-stretched sheet to obtain a porous film.

[0129] <Step (I)>

[0130] First, in step (I), after melting and kneading the polyolefin resin (A) at a temperature above the melting point and below the decomposition temperature, the non-porous sheet before stretching is obtained by molding using an extruder or the like. As a molding method for the non-porous sheet, for example, T-die molding can be cited.

[0131] In addition, when the kneaded product is cooled and formed into a sheet, the temperature of the casting roll is preferably 60°C to 150°C, more preferably 70°C to 140°C, further preferably 80°C to 130°C, and further preferably 90°C to 120°C. When the temperature of the casting roll is above the lower limit, the crystallization of the polyolefin resin (A) is fully carried out, and thus a porous structure is fully formed. On the other hand, when the temperature of the casting roll is below the upper limit, it becomes difficult to cause undesirable conditions such as the sheet being fused to the roll before stretching and breaking the film.

[0132] The speed of the aforementioned casting roll is preferably 1.0 m / min or more and 5.0 m / min or less, more preferably 1.2 m / min or more and 4.0 m / min or less, and further preferably 1.5 m / min or more and 3.0 m / min or less. By making the speed of the casting roll above the above lower limit, productivity becomes good. On the other hand, by making the speed of the casting roll below the above upper limit, it becomes easy to keep the domain in the pre-stretched sheet in a spherical shape, and becomes easy to fully form a porous structure after stretching.

[0133] <Step (Ia)>

[0134] In addition, in the present preparation method, the aforementioned step (I) may also include the following step (Ia): when the aforementioned resin composition is melt-extruded in a sheet form and is tightly bonded to a casting roll, only the two end portions of the aforementioned sheet in the width direction are tightly bonded to the casting roll, and the central portion of the aforementioned sheet in the width direction is not tightly bonded to the casting roll.

[0135] Only the two ends of the sheet are in close contact with the casting roll, and the central part of the sheet in the width direction is not in close contact with the casting roll. This makes it difficult to produce uneven contact, thereby suppressing the uneven pore formation of the stretched film and obtaining a porous film with uniform characteristics.

[0136] In step (Ia), the means for bringing only the two ends of the sheet into close contact with the casting roll is not particularly limited, but it is preferred to use a touch roll from the viewpoint of the strength of the action of pressing the molten resin to the casting roll.

[0137] <Step (II)>

[0138] Next, the obtained pre-stretched sheet is subjected to uniaxial stretching or biaxial stretching. The uniaxial stretching may be longitudinal uniaxial stretching or transverse uniaxial stretching. The biaxial stretching may be simultaneous biaxial stretching or sequential biaxial stretching.

[0139] In order to produce the present film having air permeability, stretching conditions may be selected in each stretching step, and sequential biaxial stretching, which makes it easier to control the porous structure, is more preferable.

[0140] In addition, stretching in the machine direction (MD) of the sheet is referred to as "machine direction stretching", and stretching in the direction perpendicular to the machine direction (TD) is referred to as "transverse direction stretching".

[0141] When sequential biaxial stretching is used, it is easier to control the porous structure and to achieve a balance with other physical properties such as mechanical strength and shrinkage.

[0142] The stretching temperature may be appropriately selected depending on the composition of the resin composition used, the crystal melting peak temperature, the crystallinity, and the like.

[0143] The longitudinal stretching is preferably performed at a low temperature, and the specific stretching temperature is preferably 0 to 50° C., more preferably 5 to 40° C. If the longitudinal stretching temperature is below the upper limit, stress tends to concentrate inside the domain during stretching, and pores tend to form. On the other hand, if the longitudinal stretching temperature is above the lower limit, breakage during stretching can be suppressed, which is preferred.

[0144] The longitudinal stretching ratio at low temperature is preferably 1.1 to 5.0 times, more preferably 1.2 to 4.0 times, and further preferably 1.3 to 3.0 times. By setting the stretching ratio at low temperature to be above the lower limit, pore formation proceeds, suggesting that porosity based on stretching is fully induced. In addition, by setting the stretching ratio at low temperature to be below the upper limit, breakage during stretching can be suppressed.

[0145] In addition, the longitudinal stretching can be followed by the stretching at low temperature to form a two-stage stretching process of stretching at high temperature. The specific stretching temperature at high temperature is preferably 60 to 155°C, more preferably 70 to 140°C, and further preferably 80 to 130°C. By making the longitudinal stretching temperature at high temperature above the above lower limit, film breakage during stretching can be suppressed. On the other hand, by making the longitudinal stretching temperature at high temperature below the above upper limit, pore clogging caused by stretching at low temperature can be suppressed.

[0146] The longitudinal stretching ratio at high temperature is preferably 1.1 to 5.0 times, more preferably 1.2 to 4.5 times, further preferably 1.3 to 4.0 times, and further preferably 1.3 to 3.0 times. By making the stretching ratio at high temperature above the lower limit, the pores formed by the longitudinal stretching at low temperature can be enlarged. In addition, by making the stretching ratio at high temperature below the upper limit, the properties (thickness, air permeability and mechanical properties) of the film can be adjusted to a suitable range, and film breakage during stretching can also be suppressed.

[0147] Next, the transverse stretching temperature is preferably 100 to 155° C., more preferably 110 to 150° C. By setting the transverse stretching temperature within the above range, the pores generated during the longitudinal stretching are enlarged, the porosity of the porous layer can be increased, and sufficient air permeability and mechanical properties can be obtained.

[0148] The transverse stretching ratio can be arbitrarily selected, but is preferably 1.1 to 10 times, more preferably 1.5 to 8.0 times, and further preferably 1.5 to 5.0 times. By stretching at the above transverse stretching ratio, sufficient porosity can be obtained without deforming the pores generated during longitudinal stretching.

[0149] In addition, when the film is produced by biaxial stretching, the stretch ratio of longitudinal stretching to transverse stretching is preferably set to longitudinal: transverse = 0.5 to 1.5: 1, more preferably 0.7 to 1.2: 1. If the stretch ratio is within the above range, the properties of the film (thickness, air permeability and mechanical properties) can be adjusted to a suitable range.

[0150] When longitudinal stretching is performed in two stages at low temperature and high temperature, the transverse stretching ratio (longitudinal stretching ratio at low temperature×longitudinal stretching ratio at high temperature) may be within the above range.

[0151] <Separators for power storage devices>

[0152] The porous film of the present invention is useful as a separator for an electrical storage device. That is, the separator for an electrical storage device of the present invention is formed by the porous film of the present invention. The preferred embodiment and preferred characteristics of the separator for an electrical storage device of the present invention are the same as those described in the aforementioned porous film.

[0153] <Electrical storage devices>

[0154] The power storage device of the present invention is provided with a separator for the power storage device of the present invention. Examples of the power storage device include redox flow batteries, nickel-hydrogen batteries, lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, lithium secondary batteries such as lithium ion polymer secondary batteries, aluminum electrolytic capacitors, double electric layer capacitors, and capacitor-based devices such as lithium ion capacitors. Among them, redox flow batteries and lithium secondary batteries are preferred.

[0155] Example

[0156] The porous film of the present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited thereto in any way.

[0157] <Measurement method>

[0158] (1) Thickness (film thickness) (T)

[0159] The film was cut into 10 cm squares, and the thickness was measured at 9 points using a scale with a graduation value of 1 / 1000 mm. The average value was taken as the thickness.

[0160] (2) Air permeability resistance at 25°C (air permeability (S))

[0161] Air permeability resistance was measured in accordance with JIS P8117: 2009 in an air atmosphere at 25° C. A digital Oken air permeability meter (manufactured by Asahi Seiko Co., Ltd.) was used as a measuring instrument.

[0162] (3) Porosity

[0163] The film was cut into 10 cm squares, and the density ρ1 (apparent density) was measured. The density ρ0 (true density) when the porosity was 0% was calculated. From these values, the porosity was calculated according to the following formula.

[0164] Porosity (%) = (1-ρ1 / ρ0) × 100

[0165] (4) Tensile strength and elongation at break

[0166] The measuring device uses a tensile testing machine (tensile testing machine AG-1kNXplus manufactured by Shimadzu Corporation). The test piece used is a rectangle cut from this film into a length of 100mm and a width of 10mm in the measuring direction. The two ends of the length direction of the test piece are clamped with a chuck spacing of 40mm, and stretched at a crosshead speed of 200mm / minute. The strength of the maximum point from the start of the test to the break is taken as the tensile strength, and the elongation at the break is taken as the tensile elongation at break, and measured 3 times to obtain the average value. The above-mentioned tensile test implements both the tensile test of the MD of the film and the tensile test of the TD. In addition, the values ​​of MD and TD of the tensile strength and the tensile elongation at break are averaged to obtain the average tensile strength and the average tensile elongation at break.

[0167] <Materials>

[0168] (Polyolefin resin (A)

[0169] A-1

[0170] Homopolypropylene (weight average molecular weight (Mw): 48500, molecular weight distribution (Mw / Mn): 4.43, MFR (230°C, 2.16 kg): 1.9 g / 10 min)

[0171] (Styrene-based thermoplastic elastomer (B))

[0172] B-1

[0173] Styrene-based thermoplastic elastomer (styrene-ethylene-propylene-styrene block copolymer (SEPS), weight average molecular weight (Mw): 271,000, molecular weight distribution (Mw / Mn): 1.09, MFR (230°C, 2.16 kg): no flow, MFR (200°C, 10 kg): no flow, styrene content: 20% by mass)

[0174] B-2

[0175] Styrene-based thermoplastic elastomer (styrene-ethylene-butylene-styrene random copolymer (SEBS), weight average molecular weight (Mw): 285,000, molecular weight distribution (Mw / Mn): 1.11, MFR (230°C, 2.16 kg): no flow, MFR (200°C, 10 kg): no flow, styrene content: 33% by mass)

[0176] B-3

[0177] Styrene-based thermoplastic elastomer (styrene-ethylene-propylene block copolymer (SEP), weight average molecular weight (Mw): 148,000, molecular weight distribution (Mw / Mn): 1.04, MFR (200°C, 10 kg): 1.8 g / 10 min, styrene content: 36 mass %)

[0178] B-4

[0179] Styrene-based thermoplastic elastomer (styrene-ethylene-propylene block copolymer (SEP), weight average molecular weight (Mw): 186,000, molecular weight distribution (Mw / Mn): 1.07, MFR (230°C, 2.16 kg): 0.1 g / 10 min, MFR (200°C, 10 kg): 0.1 g / 10 min, styrene content: 35% by mass)

[0180] (Crystallization nucleating agent (C))

[0181] C-1

[0182] α-crystal nucleating agent (1,3:2,4-bis-O-(4-methylbenzylidene)-D-sorbitol)

[0183] <Production of porous film>

[0184] Example 1

[0185] A mixture of 70% by mass of a polyolefin resin (A-1), 30% by mass of a styrene-based thermoplastic elastomer (B-1), and 0.1 parts by mass of a crystal nucleating agent (C-1) relative to 100 parts by mass of the resin components was added. The twin-screw extruder was melt-kneaded at a set temperature of 200°C, and then formed into a sheet with a T die. Just after the sheet landed on a casting roll set at 105°C, the two ends of the sheet were pressed with a non-driven contact roll of 5 cm in diameter and 1 cm in width to cool and solidify, thereby obtaining a pre-stretched sheet with a thickness of 100 μm. Afterwards, the pre-stretched sheet was stretched at a low temperature between a roller (X) set at 20°C and a roller (Y) set at 20°C at a ratio shown in the table. Next, between a roller (P) set at 120°C and a roller (Q) set at 120°C, high-temperature stretching was performed at a ratio shown in the table to obtain an MD stretched porous film. Next, the obtained MD stretched porous film was preheated at a preheating temperature of 145° C. and a preheating time of 12 seconds using a film tentering machine manufactured by Kyoto Machinery Co., Ltd., stretched in the transverse direction at a stretching temperature of 145° C. and at a ratio shown in the table, and then heat-treated at 155° C. to obtain a biaxially stretched porous film. The evaluation results of the obtained films are summarized in Table 1.

[0186] Embodiments 2 to 4

[0187] The contents of the polyolefin resin, the styrene-based thermoplastic elastomer and the crystallization nucleating agent were as shown in Table 1, and a pre-stretched sheet having a thickness of 100 μm was obtained in the same manner as in Example 1. Thereafter, the pre-stretched sheet obtained was stretched at the stretching ratio shown in Table 1, and a biaxially stretched porous film was obtained in the same manner as in Example 1. The evaluation results of the obtained films are summarized in Table 1.

[0188] Example 5

[0189] The casting roll was set at a temperature of 97° C., and the contents of the polyolefin resin, the styrene-based thermoplastic elastomer, and the crystal nucleating agent were as shown in Table 1. A pre-stretched sheet having a thickness of 100 μm was obtained in the same manner as in Example 1. Thereafter, the pre-stretched sheet obtained was stretched at the stretching ratio shown in Table 1. A biaxially stretched porous film was obtained in the same manner as in Example 1. The evaluation results of the obtained films are summarized in Table 1.

[0190] Reference Example 1

[0191] A pre-stretched sheet having a thickness of 250 μm was obtained in the same manner as in Example 1 except that the setting temperature of the casting roll was 127° C. Thereafter, a biaxially stretched porous film was obtained in the same manner as in Example 1 except that the pre-stretched sheet was stretched at the stretching ratio described in Table 1. The evaluation results of the obtained films are summarized in Table 1.

[0192] Reference Example 2

[0193] A pre-stretched sheet having a thickness of 100 μm was obtained in the same manner as in Example 1 except that a styrene-based thermoplastic elastomer (B-4) was used instead of the styrene-based thermoplastic elastomer (B-1) and the setting temperature of the casting roll was 127° C. Thereafter, a biaxially stretched porous film was obtained in the same manner as in Example 1 except that the pre-stretched sheet obtained was stretched at the stretching ratio described in Table 1. The evaluation results of the obtained films are summarized in Table 1.

[0194] [Table 1]

[0195] Table 1

[0196]

[0197] As shown in Table 1, in Examples 1 to 5, porous films having both air permeability and mechanical properties were obtained. These films did not cause uneven adhesion or film breakage during film production.

[0198] Examples 1 and 2 suggest that the porosity of the present composition increases and the air permeability becomes better by increasing the stretching ratio. It also suggests that the polyolefin resin (A) is oriented and the mechanical properties become better by increasing the stretching ratio.

[0199] On the other hand, Reference Example 1 attempts to improve air permeability by increasing porosity by using a thicker film than Examples 1 to 5, but the porosity is too high, so the mechanical properties are reduced, and it is impossible to achieve both air permeability and mechanical properties.

[0200] In Reference Example 2, a film having the same thickness and porosity as those of the example can be produced, but the combination of the polyolefin resin (A) and the styrene thermoplastic elastomer (B) reduces the mechanical properties, and it is impossible to achieve both air permeability and mechanical properties.

[0201] (5) Thermal shrinkage

[0202] For the porous films prepared in Examples 1 to 4, samples were cut so that the longitudinal direction (MD) and the transverse direction (TD) were 150 mm in length and 10 mm in width, respectively, and the marking lines were marked at intervals of 100 mm in such a way that the center of the longitudinal direction was centered relative to the longitudinal direction. After that, the film was heated in an oven at 60°C for 1 hour, and the spacing between the marking lines after shrinkage was measured. The measured spacing between the marking lines was substituted into the following formula to calculate the shrinkage rate (%). The average value of the shrinkage rates obtained for the longitudinal direction (MD) and the transverse direction (TD) was taken as the thermal shrinkage rate, and the results are shown in Table 2.

[0203] Shrinkage rate (%) = ((marking line interval before shrinkage - marking line interval after shrinkage) / marking line interval before shrinkage) × 100

[0204] [Table 2]

[0205] Table 2

[0206]

[0207] As shown in Table 2, in Examples 1 to 4, porous films having a small heat shrinkage ratio and excellent dimensional stability were obtained.

[0208] It is suggested that the porous film of Example 4 using the styrene-olefin copolymer (B1) and the styrene-olefin-styrene block copolymer (B2) as the styrene-based thermoplastic elastomer (B) is particularly excellent in dimensional stability.

Claims

1. A porous film comprising a polyolefin resin (A) and a styrene-based thermoplastic elastomer (B), The porous film has a thickness (T) of less than 50 μm, an average tensile strength of more than 15 MPa, an average tensile elongation at break of more than 35%, and a ratio (S / T) of air permeability (S) (seconds / 100 cc) to thickness (T) (μm) of more than 0.15 and less than 1.

45. 2 . The porous film according to claim 1 , which has an average tensile strength of 25 MPa or more.

3. The porous film according to claim 1, wherein The polyolefin-based resin (A) is homopolypropylene.

4. The porous film according to claim 1, wherein The styrene-based thermoplastic elastomer (B) contains the styrene-olefin-styrene block copolymer (B2) in a ratio of 50% by mass or more when the total amount of the styrene-based thermoplastic elastomer (B) is 100% by mass.

5. The porous film according to claim 1, wherein The styrene content of the styrene-based thermoplastic elastomer (B) is 10% by mass or more and 40% by mass or less.

6. The porous film according to claim 1, wherein The styrene-based thermoplastic elastomer (B) contains a resin having a weight average molecular weight (Mw) of 200,000 or more in a ratio of 50% by mass or more when the total amount of the styrene-based thermoplastic elastomer (B) is 100% by mass.

7. The porous film according to claim 1, wherein The styrene-based thermoplastic elastomer (B) contains a resin having a melt flow rate (MFR) of less than 0.1 g / 10 min or no flow at 200° C. and a load of 10 kg, accounting for 50% by mass or more of the total amount of the styrene-based thermoplastic elastomer (B) as 100% by mass.

8. The porous film according to claim 1, wherein The styrene-based thermoplastic elastomer (B) comprises a styrene-olefin copolymer (B1) and a styrene-olefin-styrene block copolymer (B2), wherein the styrene-olefin copolymer (B1) has a melt flow rate (MFR) of 1.0 g / 10 min or more measured at a temperature of 200° C. and a load of 10 kg.

9. The porous film according to claim 1, wherein The content of the polyolefin-based resin (A) is 60% by mass or more and 95% by mass or less.

10. The porous film according to claim 1, wherein The content of the styrene-based thermoplastic elastomer (B) is 5% by mass or more and 40% by mass or less. 11 . The porous film according to claim 1 , further comprising a crystal nucleating agent (C).

12. The porous film according to claim 1, which has an air permeability (S) of 50 sec / 100 cc or less. 13 . A separator for an electricity storage device, comprising the porous film according to claim 1 . 14 . An electricity storage device comprising the separator for an electricity storage device according to claim 13 .